PENGARUH KEMANDIRIAN BELAJAR TERHADAP HASIL BELAJARSISWA KELAS IV DI SDN 6 DAWUHANKECAMATAN SITUBONDO TAHUN PELAJARAN 2017/2018 - Yeni Rahmaniyah; Heldie Bramantha (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Abdurachman Saleh Situbondo, 2018)
This study aims to determine whether there is influence of learning independence on student learning outcomes of The 4thgrade students SDN 6 Dawuhan academic year 2017/2018. This research is a quantitative research, The method used is comprative. The formulation of the problem in this research is whether there is influence of learning independence on student learning outcomes of The 4thgrade students SDN 6 Dawuhan academic year 2017/2018?. The population in this study were students at SDN 6 Dawuhan. This research use purpusive sampling technique, with sample number 30 responden (all student of class 4th). This research consist of independent variable and dependent variable, independent variable that is learning independence (X), and dependent variable that is learning outcomes (Y). Data collection technique used in this study is using questionnaires and documentation (student learning outcomes). The results showed that the influence of learning independence on student learning outcomes of class 4th is in the category of influence is it can be in known from the correlation coefficient of R = 0,507, and to know whether the hypothesis submitted accepted / rejected, then T count compared with T table with significant level of 0,005 with the number of respondents 30 obtaided T table = 2,048 whereas T count = 3,117, means T count 3,117 > T table 2,048 so (Ho) is rejected and (Ha) accepted. Based on the results of the study, then this study, concluded (Ho) rejected and (Ha) accepted, that there is Influence Of Learning Independence On Student Learning Outcomes Of The 4thGrade Students SDN 6 Dawuhan Academic Year 2017/2018